Profile of visual impairment in children attending low vision clinic of Nepal Eye Hospital - Sapkota, Kishore; Rajkarnikar, Sagar; Shrestha, Bina; Panthi, Shyam; Pokharel, Archana (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Visual impairment (VI) in children accounts for great challenge in the life of children that leads to greater medical, psychological, social and economic problems since the child has to live up with handicap for many years to come. Identifying the main causes of visual degradation and their pattern will help in preventive measures, early diagnosis, treatment and rehabilitation of vulnerable population. The aim of this study was to find out the pattern of visual impairment in children attending low vision clinic of Nepal Eye Hospital. Methods: A retrospective cross--sectional review of hospital records of all VI children att ending the low vision clinic from 1st May 2010 to 31st April 2011 with age less than 16 years was done. Results: Overall, 65 children were included in this study with mean age 11.58±3.83 years. Among them 55.4% were male. More than one third (34%) of the total children were in the category of blindness. More than two thirds (72.30%) patients had refractive error. Majority of the patients (66.15%) had multiple causes of visual impairment. Major causes of visual impairment were nystagmus (58.46%), high refractive error (26.15%) and amblyopia (24.61%). Low vision devices were prescribed for only 18.46% of the total patients. Telescope was the most frequently prescribed low vision optical device. Conclusion: Nystagmus, high refractive error and amblyopia were the main causes of VI. Most of the cases had multiple causes. Low vision devices were prescribed for very few of the visual impaired patients and telescope was the most frequently prescribed among them. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6458 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 18-21